2019
DOI: 10.1590/0103-8478cr20180729
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Lactobacillus acidophilus and different prebiotic agents by external ionic gelation followed by freeze-drying

Abstract: The aim of this study was to investigate the influence of the addition of prebiotics rice bran, inulin and hi-maize, on the survival of Lactobacillus acidophilus in alginate microparticles obtained by external ionic gelation followed by freeze-drying. The microparticles size ranged from 127.5μm to 234.6μm. Microparticles added from the different prebiotics demonstrated an increase in the protection of the microorganism, which presented greater viability against the gastrointestinal simulation. As for storage u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
12
0
2
Order By: Relevance
“…However, the size of the microbeads produced from extrusion had a wider range of 127.5–3110 μm, whereas the size of the microbeads produced from co‐extrusion had a closer range of 423–805 μm as shown in Table 3. We observed that all probiotics encapsulated using the co‐extrusion technique were below 1000 μm, whereas most of the probiotics encapsulated using the extrusion technique were above 1000 μm, except for Bekhit et al (2016), Chávarri et al (2010), Poletto et al (2019), and Silva et al (2018).…”
Section: Effects Of Microencapsulationmentioning
confidence: 82%
See 2 more Smart Citations
“…However, the size of the microbeads produced from extrusion had a wider range of 127.5–3110 μm, whereas the size of the microbeads produced from co‐extrusion had a closer range of 423–805 μm as shown in Table 3. We observed that all probiotics encapsulated using the co‐extrusion technique were below 1000 μm, whereas most of the probiotics encapsulated using the extrusion technique were above 1000 μm, except for Bekhit et al (2016), Chávarri et al (2010), Poletto et al (2019), and Silva et al (2018).…”
Section: Effects Of Microencapsulationmentioning
confidence: 82%
“…The smaller size microbeads produced by Chávarri et al (2010), Poletto et al (2019), and Silva et al (2018) could be due to the addition of drying techniques (freeze drying and fluidized bed drying) after the extrusion encapsulation. As freeze drying or fluidized bed drying would reduce moisture from the microbeads, it would result in smaller bead size (Darvishi et al, 2015; Pang et al, 2017).…”
Section: Effects Of Microencapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbiotic microparticles are capable of increasing the survival rates of probiotic microorganisms after exposure to simulated gastrointestinal tract (POLETTO et al, 2019). Among the existing prebiotics, it is possible to highlight inulin, Hi-maize, galacto-oligosaccharides (GOS), fructo-oligosaccharides (FOS), xylooligosaccharides, pectin, lactulose, soy oligosaccharides, and lactitol xylitol (SIRÓ et al, 2008).…”
Section: Symbiotic Foodsmentioning
confidence: 99%
“…For example, Shinde et al [42] obtained diameters ranging from 423 to 486 µm for the co-extrusion encapsulation of probiotic Lactobacillus acidophilus with apple skin polyphenols. In addition, microparticles ranging from 127.5 to 234.6 µm were produced for the co-encapsulation of Lactobacillus acidophilus and different prebiotic agents by external ionic gelation followed by freeze-drying [43]. In addition, Gaudreau et al [44] reported microparticles ranging from 81 to 130 µm when probiotic Lactobacillus helveticus was co-encapsulated with green tea extract in calcium pectinate microparticles by the emulsification/internal gelation technique.…”
Section: Particle Size and Zeta-potentialmentioning
confidence: 99%